The Sibyls from the church of San Pedro Telmo: a micro-Raman spectroscopic investigation - Marte, Fernando Daniel (2014)
The series of the Sibyls from the church of San Pedro Telmo is one of the most important groups of paintings of Argentine colonial art. Ten of the paintings were performed in the 18th century, while those corresponding to the Delphic and Tiburtine Sibyls were painted in 1864 during the first restoration of the series in Buenos Aires. There is a controversy regarding the origin of this remarkable group of paintings pointing to an Andean workshop or a Spanish source. In this study, Raman microscopy in combination with scanning electron microscope energy-dispersive X-ray spectrometer analysis and HPLC has successfully identified the materials employed in the manufacture of the paintings. The Raman analysis revealed the presence of a mixture of barium sulfate, lead white, and calcite in the preparation layers of the 19th century Sibyls in contrast to the clayish ground layer in the 18th century paintings. Traditional pigments such as vermilion, lead white, orpiment, indigo, ultramarine blue, and Prussian blue were readily identified by Raman microscopy. The presence of a madder lake in one of the 18th century Sibyls strongly suggests their Spanish origin in accordance with historical data. The identification of synthetic ultramarine blue in the Tiburtine painting is the first report of this blue pigment in Argentine colonial art.